Process Analytical Instrumentation, the Challenges for In-situ Characterization of Complex Particulate Materials. (2015) - Richard, J.; Tweedie
Abstract: The twin desires to increase competitiveness, and reduce exposure to risk are common to all manufacturers. This translates into increasing product complexity, a constant pressure on costs, and legislated minimisation of environmental footprint which in turn requires better control, more cheaply and with less waste. Hence improving process efficiency and understanding is a key goal for many chemical producers. Particulate handling operations are widespread in the processing of a wide and diverse range of products, including pharmaceuticals, foodstuffs, household, and speciality chemicals with up to 60% of the chemical business involving particle processing. Therefore analytical particle technology has always had an important role to yield microstructure information of such complex materials. There is a widespread perceived industrial need to develop and deliver fast, reliable and accurate tools and methods for the in-situ characterisation of particulate processes and products. The justification being that end-product quality and reproducibility depends on determining the concentration of the solution, the solids, particle size distribution, as these factors dictate the individual process efficiency and have a major impact on downstream operations such as filtration, drying, transport, and storage. While offline characterisation of processes provides a more controlled environment, by definition the product is removed from the process environment, on-line characterisation offers direct observation in process conditions but at the cost of losing control of the measurement environment and the material ceasing to be the ideal, well behaved sample. Process Analytical instruments should be an essential part of the solution especially at high concentration where real industrial processes operate and should demonstrate significant uptake in on-line analysis. But despite all the claims and all the hopes, in the last 15 years the capability to characterise particulate systems in-situ at high concentration has not met with the original expectations. We examine the benefits of replacing off-line analytical procedures with on-line size analysis systems, the challenges of characterising complex and high concentration processes and describes some of the novel technologies being developed to provide not only information on the structure but also on the process performance. Simple adaption of laboratory methods has significant disadvantages, especially at High Concentration which is the typical process situation. There remains a significant challenge in applying novel solutions to provide a more complete and instantaneous picture of both the nature of the product and the process. We examine the progress in the field, the issues; the needs and the factors which must be considered to achieve a successful solution to real applications.